Analisis Faktor Spesifik Bank Terhadap Non Performing Loan Pada Bank Umum Konvensional Yang Terdaftar Di Bursa Efek Indonesia - Meily Juliani (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this research is to analyze the effect of bank specific factors on non-performing loan on public conventional banks. The dependent variable studied was the non-performing loan and independent variables examined were capital adequacy ratio, bank size, loan to deposit ratio, net interest margin, return on equity, operating expenses to operating income, and earning per share. The secondary data obtained from the annual reports submitted in the IDX. Sample consist of 32 public conventional banks listed in IDX in the period of 2012-2017. The result of this study indicate that bank size and net interest margin has a positive and significant impact on non-performing loan. While return on equity showed a negative and significant impact on non-performing loan. The result of this study also showed that capital adequacy ratio, loan to deposit ratio, operating expenses to operating income and earning per share did not have any significant impact on non-performing loan.